Indicadores de produção científica para prospecção tecnológica em manufatura aditiva de biocerâmicas - Porto, André Candido (2019)
In the Bone Tissue Engineering, biomaterials are used as scaffolds to produce a support and cell growing. Because of the similarity to the bones cells, ceramic compounds are the main materials used to produce the scaffold. However, the primary challenge of producing them relies on conformation, due to anatomical complex geometry. Under this perspective, the additive manufacturing technology (AM) is seen as a solution, because of its conformational liberty of parts production. Thus, a technological forecasting establish a scene of the AM researches in development and understate the uncertain towards the future of bioceramics application. This research aims to map the scientific and technological progress of bioceramics use in AM trough scientific indicators made in the technological forecasting context. The methodology is based on the use of bibliometry in a recordset of scientific publications indexed in the Web of Science database, and as complement, AM experts evaluations were used to arbitrate the scientific method. The recovered records were filtrated and classified by traditional scientific indicators and by text mining, the extraction of AM and bioceramics were made to produce advanced scientific indicators. The indicators analysis revealed a global tendency of growth in scientific papers of AM, with USA, China and Germany as the main countries with research in this topic. Brazil is the 20th country in this scenario, with the South and Southeast public education institutes as main agents. Regarding AM technologies the Powder Bed Fusion and Vat Polymerization, nonetheless the general processes were the one with the highest number of publications. The recurrent bioceramics were Calcium Phosphates, Alumina, Zirconia and a highlight to the glass and glass ceramics.